(untitled) (Bangladesh Journal of Pharmacology, 2021)
The aim of this study was to explore the possible molecular mechanisms of paeonol in preventing ventricular remodeling. The cell viability of neonatal rat cardiac fibroblasts was detected by the method of MTT. RT-PCR and Western blot were used to measure the expression of TGF-β1, type I collagen and type III collagen. After treating the cardiac fibroblasts with paeonol, the cell viability decreased (p<0.01), and the expression of TGF-β1, type I collagen and types III collagen was significantly reduced (p<0.01). Thus, paeonol can inhibit the proliferation of fibroblast cells induced by aldosterone. The molecular mechanism is related to the down-regulation of TGF-β1 and type I and III collagen gene expression.